2010
DOI: 10.1097/bcr.0b013e3181f9353a
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells and Burns: Review and Therapeutic Implications

Abstract: Despite significant advances in burn resuscitation and wound care over the past 30 years, morbidity and mortality from thermal injury remain high. Limited donor skin in severely burned patients hinders effective wound excision and closure, leading to infectious complications and prolonged hospitalizations. Even with large-volume fluid resuscitation, the systemic inflammatory response syndrome compromises end-organ perfusion in burn patients, with resultant multiorgan failure. Stem cells, which enhance wound he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 97 publications
0
59
0
1
Order By: Relevance
“…36,40,41 However, in this study a local injection route was preferred for the treatment and the systemic cytokine levels were not altered. The effect of local stem cell administration upon systemic cytokine levels still has to be investigated.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…36,40,41 However, in this study a local injection route was preferred for the treatment and the systemic cytokine levels were not altered. The effect of local stem cell administration upon systemic cytokine levels still has to be investigated.…”
Section: Discussionmentioning
confidence: 76%
“…However, further investigations were indicated to exhibit this regulatory effect. 10,36,40 Reported studies demonstrated that severe burn injuries, namely those affecting 40 percent and more of body surface area, were leading to a hypermetabolic state resulting in a cytokine response parallel to the severity of the burn. [37][38][39] In this presented study, cytokine response following the applied burn model and the effect of mesenchymal stem cell treatment on the cytokine levels were also investigated.…”
Section: Discussionmentioning
confidence: 98%
“…Stem cell therapies in wound care may lessen these morbidities (18). Specifically, the burn wound has unique characteristics that have to be considered when designing a clinical trial for stem cell therapy applications: it is an ischemic wound, with an altered pH and temperature, prone to infection and development of chronic sequel, such as non-healing ulcers and hypertrophic scarring (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reveal that thymoquinone helps inhibit the production of arachidonic acid and that it has anti-lipid peroxidation and anti-tumor effects (Butler et al, 2010;Singer et al, 2011). Information regarding the protective effect of thymoquinone and its mechanism of action in cholestatic liver cells is lacking.…”
Section: Introductionmentioning
confidence: 99%